Nonalcoholic fatty pancreas disease is related independently to the severity of acute pancreatitis. Issue 8 (August 2019) - Xie, Jiarong; Xu, Lu; Pan, Yuning; Li, Peifei; Liu, Yi; Pan, Yue; Shan, Keshu; Zhang, Yu; Xu, Lei
Abstract : Background: This study aimed to investigate the association between nonalcoholic fatty pancreas disease and the severity of acute pancreatitis (AP). Patients and methods: Among the 1662 AP patients admitted between August 2010 and August 2017, 82 eligible patients with moderately severe acute pancreatitis (SAP) and SAP were selected. Meanwhile, 164 mild AP patients were age-matched, sex-matched, and BMI-matched at a ratio of 1 : 2. Nonalcoholic fatty pancreas disease was estimated by mean pancreas attenuation by unenhanced computed tomography. Finally, 1662 patients were screened and 246 patients were analyzed. Results: For the 246 patients, the mean pancreatic attenuation and pancreas-to-spleen attenuation ratio (P/S ratio) were significantly lower in the moderately SAP and SAP groups compared with those in the mild AP group (both, P <0.001). Pancreatic attenuation decreased with an increase in the rate of ICU transfer, AP severity, systemic complications, and prognostic factors of AP (Acute Physiology and Chronic Health Evaluation II score≥8; P <0.001). A decreased P/S ratio was correlated positively with the increased mortality of patients with AP (hazard ratio: 0.000; 95% confidence interval: 0.000–0.012; P <0.001), as determined by Cox proportional regression analysis adjusted for creatinine, calcium, and albumin levels. Conclusion: The pancreatic attenuation level and P/S ratio are correlated independently to severity, mortality, and systemic complications in patients with AP.